¿Por qué son necesarias unidades geriátricas de agudos en el sistema de salud chileno? - Hidalgo A., Jaime (Revista Hospital Clínico Universidad de Chile, 2015)
For centuries, man has been concerned about health, particularly to achieve successful aging. In this process of health and illness, often the elderly were dying in the attempt to improve, and those requiring more care, it was not possible to do at home, so they sought the help of others, most of whom were Monasteries, which later gave way to hospices, Nurse Homes and Hospitals. Given the growing senior population that required hospital care and elderly care was developing Geriatrics, along with a comprehensive model of confrontation and interdisciplinary intervention, soon found in geriatric acute care setting, the core specialty. Over the past 50 years, it has become clear that in conjunction with the Integral Geriatric Evaluation, these units have shown a change in the prognosis of the elderly. Since Chile is experiencing a rapidly aging population, it is necessary to develop these units in our health care system.